Leader Value Added : Assessing the Growth Contribution of Individual National Leaders - Easterly, William; Pennings, Steven (World Bank, Washington, DC, 2020)
Previous literature suggests that leaders matter for growth in general. This paper asks which leaders matter and develops a methodology to estimate the growth contribution of individual leaders and calculate its precision. The findings show that few leaders have statistically significant contributions; it is difficult to know who is good for growth and who is not. The paper also finds that the most intuitive estimate of a leader’s contribution—the average growth rate during tenure—is largely useless for measuring his or her true contribution. Consequently, many leaders with statistically significant growth effects are surprises. Moreover, leaders in non-democratic countries are no more likely to be statistically significant than leaders in democratic ones.